2023
DOI: 10.3389/fsurg.2023.1115139
|View full text |Cite
|
Sign up to set email alerts
|

Indications and technical aspects of proximal gastrectomy

Abstract: According to the World Health Organization, gastric cancer is the fifth most common type of tumor, and is the third most common cause of tumor-associated death. Although gastric cancer incidence rates have decreased in the past few decades, the prevalence of proximal gastric cancer has been steadily rising in developed countries. Techniques regarding the improvement of treatment options must thus be developed. This can be achieved through incorporating both a wider use of endoscopic surgery (endoscopic mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…26 Furthermore, several retrospective studies show that PG is superior to TG in maintaining body weight and preserving QOL. 6,27 For example, Takiguchi, et al compared postoperative QOL between TG (n = 393) and PG (n = 193) and found that PG achieved better QOL with less diarrhea and dumping symptoms, less weight loss, and less necessity for additional meals. 23 Nakada, et al reported that PG compared with TG was associated with diminished adverse effects on QOL, as assessed using a PGSAS questionnaire, resulting in less impairment of daily living.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Furthermore, several retrospective studies show that PG is superior to TG in maintaining body weight and preserving QOL. 6,27 For example, Takiguchi, et al compared postoperative QOL between TG (n = 393) and PG (n = 193) and found that PG achieved better QOL with less diarrhea and dumping symptoms, less weight loss, and less necessity for additional meals. 23 Nakada, et al reported that PG compared with TG was associated with diminished adverse effects on QOL, as assessed using a PGSAS questionnaire, resulting in less impairment of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several retrospective studies show that PG is superior to TG in maintaining body weight and preserving QOL. 6,27 For example, Takiguchi, et al. compared postoperative QOL between TG ( n = 393) and PG ( n = 193) and found that PG achieved better QOL with less diarrhea and dumping symptoms, less weight loss, and less necessity for additional meals 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations